Use of ECG Restitution (Beat-to-Beat QT-TQ Interval Analysis) to Assess Arrhythmogenic Risk of QTc Prolongation with Guanfacine - Fossa, Anthony A.; Zhou, Meijian; Robinson, Antoine; Purkayastha, Jaideep; Martin, Patrick (Annals of noninvasive electrocardiology, 2014)
Background Guanfacine (Intuniv) is a centrally active alpha‐2A adrenergic agonist for the new indication of attention‐deficit/hyperactivity disorder. QTc (QTcF and QTcNi) was prolonged at both therapeutic (4 mg) and supratherapeutic (8 mg) doses of a thorough QT study even though guanfacine has had a safe clinical history of over 3 million prescriptions for the treatment of hypertension. In an attempt to understand this disparity, retrospective evaluation of the continuous ECG data utilized dynamic beat‐to‐beat and ECG restitution analyses was performed. Methods Sixty healthy subjects using 24‐hour Holters were examined in a 3‐arm, placebo‐ and positive‐controlled, double‐blind crossover study for effects on beat‐to‐beat QT, TQ, and RR intervals. Results ECG restitution analyses indicated that, at all time points, a disproportionate effect to increase the TQ interval (rest) occurred more in relationship to each QT interval lengthening resulting in a placebo‐adjusted reduced QT/TQ ratio of 21% after 4 mg and 31% after 8 mg (both antiarrhythmic responses). Additionally, the percentage of time and magnitude of stress on the heart, as measured by the upper limits of the QT/TQ ratio, were reduced with guanfacine by 22% to 24%. In contrast to guanfacine, moxifloxacin did not show a significant improvement in any restitution parameters but reflected a trend toward proarrhythmia with an increase in the QT/TQ ratio of up to 11%. Conclusion These results indicate that guanfacine causes a stabilizing effect on cardiac restitution that helps reconcile the clinical evidence for a lack of arrhythmia liability despite apparent increases in typical QT/QTc prolongation measures.